Clusterin promotes the aggregation and adhesion of renal porcine epithelial cells. - Silkensen, J R; Skubitz, K M; Skubitz, A P; Chmielewski, D H; Manivel, J C; Dvergsten, J A; Rosenberg, M E (The Journal of Clinical Investigation, 1995)
The function of clusterin, a heterodimeric glycoprotein markedly induced in renal and other organ injuries, is unclear. Since renal injury is accompanied by alterations in cell attachment, it is possible that clusterin functions to promote cell-cell and cell-substratum interactions. In this study, a single cell suspension of renal epithelial (LLC-PK1) cells was treated with purified human clusterin, resulting in time- and dose-dependent cell aggregation. Electron microscopy of the cell aggregates demonstrated cell junction and lumen formation. To determine the effect of clusterin on cell adhesion, tissue culture plates were coated with clusterin, fibronectin, PBS, or albumin. Clusterin and fibronectin promoted cell adhesion to the same extent. The adhesion to clusterin was dose dependent and specific, as a monoclonal antibody against clusterin inhibited cell adhesion to clusterin but not fibronectin. Perterbations of the cytoskeleton may underlie the alterations in cell attachment which occur in renal injury. Induction of clusterin mRNA was seen after disruption of both microtubules and microfilaments and after inhibition of cell-substratum interactions. In conclusion, clusterin is a potent renal epithelial cell aggregation and adhesion molecule. We speculate that clusterin functions to promote cell-cell and cell-substratum interactions which are perturbed in the setting of renal injury, thereby preserving the integrity of the renal epithelial barrier. Images